Numerical investigation on heat transfer of supercritical carbon dioxide in a vertical tube under circumferentially non-uniform heating. (25th June 2018) - Fan, Y.H.; Tang, G.H.
Highlights: Heat transfer of supercritical carbon dioxide with non-uniform heating is simulated. Difference in localized heat transfer between top and bottom generatrix is large. Mokry correlation and Gupta correlation can be extended for non-uniform heating. Heat transfer performance is closely related to local thickness of viscous sublayer. A new heat transfer correlation for non-uniform heating is proposed. Abstract: Heat transfer characteristics of supercritical carbon dioxide in circumferentially non-uniform heated vertical upward flow near critical point are reported. Stainless steel tube with internal diameter of 38 mm is numerically investigated for mass flow rate from 1000 to 2000 kg/(m 2 ·s), heat flux from 100 to 400 kW/m 2 and pressure from 81.94 to 150 bar. Circumferential thermal conduction in solid region has a significant impact on non-uniform heating, but a weak impact on uniform heating. Comparisons among the empirical Nusselt correlations for uniform heating show that the Mokry and Gupta correlations can capture severe heat transfer impairment at top generatrix fairly well under non-uniform heating. The existing buoyancy criterions to distinguish forced and mixed convection cannot be applied directly to evaluate buoyancy effect in present conditions. Moreover, the mechanism for severe heat transfer deterioration is discussed. Detailed axial velocity and turbulences show that the buoyancy effect should still be considered even in fully developed forced convection and the turbulent kinetic energy tends to have less impact on heat diffusion. Local thickening of the viscous sublayer reduces the effectiveness of heat diffusion seriously. Meanwhile, the decreasing Prandtl number induced by temperature rise further weakens the heat diffusion in viscous sublayer. Finally, a new heat transfer correlation for non-uniform heating is proposed by introducing the viscosity correction.